PENGEMBANGAN MEDIA PEMBELAJARAN MICROSITE BERBASIS DEEP LEARNING UNTUK BAHASA INGGRIS SD - Apriliyani, Shanti; Taufiqulloh; Khusnul Khotimah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The increasing integration of digital technologies has reshaped teaching methods in elementary schools, especially for English learning. Traditional approaches that rely mainly on textbooks and teacher-centered instruction often restrict students’ participation and independent learning. This study focuses on the development of a microsite-based digital learning media incorporating a Deep Learning framework to facilitate English instruction for elementary students. The research followed a Research and Development (R&D) design, covering the Analysis, Design, and Development phases of the ADDIE model. Data were obtained through observations, interviews, questionnaires, and documentation involving lecturers, peers, and students to determine learning requirements, conduct content validation, and evaluate practicality. Expert assessments were performed to ensure the alignment of learning materials, instructional design, and media quality, while practicality testing captured user feedback on usability, material clarity, visual appeal, and support for autonomous learning. Results demonstrate that the microsite-based media is both feasible and practical for classroom use. It promotes students’ autonomy, motivation, and engagement in learning English while offering educators a well-structured, interactive digital resource. These findings highlight that applying Deep Learning principles in microsite development can provide innovative and effective solutions for digital learning in elementary education.